A phenomenological reply to Gary Marcus and Ernest Davis’s Rebooting AI: building artificial intelligence we can trust: contributing to the creation of general artificial intelligence - Trujillo, Joaquin (Creativity Studies, 2023)
Marcus and Davis’s Rebooting AI: Building Artificial Intelligence We Can Trust (2019) describes the narrowness of current artificial intelligence, posits constituents of human intelligence it contends artificial intelligence (AI) must reproduce to achieve a general (broad) formulation, and envisages the contributions of general AI to human living. This article (1) reviews Marcus and Davis’s argument, (2) phenomenologically evaluates their interpretation of human intelligence, and (3) discloses the moral inconsistencies implied by their vision of the relation between general AI and human being. Transcendental and hermeneutic phenomenological perspectives are employed to address the range of phenomena the authors affiliate with human intelligence.